2020
DOI: 10.3390/vaccines8020187
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the cpsE and endA Genes Attenuates Streptococcus pneumoniae Virulence: Towards the Development of a Live Attenuated Vaccine Candidate

Abstract: The majority of deaths due to Streptococcus pneumoniae infections are in developing countries. Although polysaccharide-based pneumococcal vaccines are available, newer types of vaccines are needed to increase vaccine affordability, particularly in developing countries, and to provide broader protection across all pneumococcal serotypes. To attenuate pneumococcal virulence with the aim of engineering candidate live attenuated vaccines (LAVs), we constructed knockouts in S. pneumoniae D39 of one of the capsular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 84 publications
0
18
0
Order By: Relevance
“…29 Within this operon, the cpsE locus encodes an enzyme responsible for the addition of activated sugars to a lipid carrier in the bacterial membrane. 29 Previous work in the human pathogen S. pneumoniae has shown that a single nucleotide base substitution (C to G at the 1135 nucleotide position) in the cpsE locus results in an amino acid change from arginine to glycine at residue 379 in the CpsE protein, rendering the CpsE protein enzymatically inactive. This single nucleotide polymorphism (SNP) is responsible for the lack of capsule production.…”
Section: ■ Discussionmentioning
confidence: 74%
“…29 Within this operon, the cpsE locus encodes an enzyme responsible for the addition of activated sugars to a lipid carrier in the bacterial membrane. 29 Previous work in the human pathogen S. pneumoniae has shown that a single nucleotide base substitution (C to G at the 1135 nucleotide position) in the cpsE locus results in an amino acid change from arginine to glycine at residue 379 in the CpsE protein, rendering the CpsE protein enzymatically inactive. This single nucleotide polymorphism (SNP) is responsible for the lack of capsule production.…”
Section: ■ Discussionmentioning
confidence: 74%
“…These included glf, cpsE, cpsI, cpsA, cps4C, cps8P and hasC. The glf gene is involved in the biosynthesis of unusual monosaccharide galactofuranose [92]; cpsE codes a glycosyl transferase responsible for the addition of activated sugars to the lipid carriers in the bacterial membrane and are essential for encapsulation in S. pneumoniae [93]; cpsI is essential for the production of high molecular weight capsular polysaccharides [94]; cpsA and cps8P are necessary for normal cell wall integrity and composition [95]; cps4C codes a polysaccharide tyrosine kinase adaptor protein that plays a key role in the regulation of capsule biosynthesis [96]; finally, hasC is involved in biosynthesis of hyaluronic acid capsule biosynthesis encodes glucose-1phosphate uridylyltransferase [97].…”
Section: Virulence Factors and Principal Component Analysismentioning
confidence: 99%
“…CRISPRs also differed among strains but the DR regions were similar for a given CRISPR element subtype. Based on the type of cas proteins, the CRISPRs of strains G1562, G1563, G1564, G1556, G1554, 631_ SCON, 30,309 were subtype I-C CRISPRs; those of strains FDAARGOS_233 and KCOM1545 were subtype II-A CRISPRs; finally, the CRISPRs of strains G1565, G1552, B196, G1555 and 32811were subtype II-C CRIS PRs [93] (Table 5).…”
Section: Crispr Identification Analysismentioning
confidence: 99%
“…In the presence of influenza, vaccine protection was dramatically reduced [17,30,31]. Vaccine variations, such as immunization with pneumococcal surface protein A (PspA), engineered live-attenuated vaccines, and dual vaccine/cytokine administration, have been shown to fully protect influenza-infected mice against a physiologically relevant dose of S. pneumoniae [31][32][33]. Taken together, the cascade of innate and adaptive immune responses to an immune imprinting event can greatly impact host susceptibility to secondary infection [7].…”
Section: Introductionmentioning
confidence: 99%